2017
DOI: 10.1089/cyber.2016.0194
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Internet Attachment, Cyber Victimization, and Internalizing Symptoms Among Adolescents

Abstract: With increasing frequency of Internet use among adolescents, there are growing concerns about their risk for becoming attached to these forms of communication and increased vulnerability for negative online experiences, including cyber victimization. The effect of these experiences on adolescent mental health is not well understood. In this study, we examine how Internet attachment is related to anxiety and depression and assess the mediating effect of cyber victimization on these associations. Participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
3
11
0
4
Order By: Relevance
“…In the present study, anxiety, depression, negative self-esteem, somatization, and hostility subscale mean scores were found to be high for the adolescents who enacted cyberbullying and those who were exposed to cyberbullying. The results of the study support the literature and cyberbullying negatively affects the mental health of adolescents (Fahy et al, 2016;Holfeld & Sukhawathanakul, 2017;Landoll et al, 2015;Sari & Camadan, 2016;Ybarra & Michell, 2004;Vieno et al, 2014;Wang et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, anxiety, depression, negative self-esteem, somatization, and hostility subscale mean scores were found to be high for the adolescents who enacted cyberbullying and those who were exposed to cyberbullying. The results of the study support the literature and cyberbullying negatively affects the mental health of adolescents (Fahy et al, 2016;Holfeld & Sukhawathanakul, 2017;Landoll et al, 2015;Sari & Camadan, 2016;Ybarra & Michell, 2004;Vieno et al, 2014;Wang et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…The situation of being a victim of a cyber attack presents a stressful event for victims who are likely to experience negative feelings such as anger, fear, sadness, insecurity and shame often accompanied with the feeling of surprise [124]. In a study on adolescents [135], it was found that those with greater Internet attachment were more likely to experience cyber victimisation and greater symptoms of anxiety and depression. With reliance on IoT devices in the home, it is important to take such results into account to develop strategies for decreasing negative impacts of attachment to IoT technology and possible emotional difficulties.…”
Section: E-sf: Subjective Feelingmentioning
confidence: 99%
“…Prior research has identified media exposures, such as video games, television, movies, and the Internet, to be associated with the development of depression among adolescents (Bickham et al, 2015; Gonzálvez et al, 2016; Holfeld and Sukhawathanakul, 2017; Liu et al, 2016; Primack et al, 2009). Other research has extended this by suggesting that use of social media is associated with depressive symptoms and a decline in well-being among both adolescents (Pantic et al, 2012) and adults (Kross et al, 2013; Lin et al, 2016; McDougall et al, 2016; Shensa et al, 2016).…”
mentioning
confidence: 99%